Integrasi Psikologi dalam Manajemen Sumber Daya Manusia: Systematic Literature Review tentang Stres Kerja, Motivasi dan Kinerja Organisasi - Intan Zayinatun Nisa; Abd Hasib; Muallimin Muallimin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2026)
The development of modern organizations requires the integration of psychological aspects into management practices in order to enhance individual performance and well-being. Issues such as work stress, motivation, and psychology-based leadership have become increasingly important in responding to the dynamics of complex work environments. This study aims to examine the development and trends in management psychology and to identify its contributions to organizational practices. The research questions posed are: (1) how has management psychology research developed over the past five years, and (2) what are the main themes and their contributions to organizational management. The method used is a qualitative approach with a literature review through the Google Scholar and Publish or Perish databases using the keyword “management psychology.” A total of 20 articles were obtained, then selected through a screening and eligibility process, resulting in 5 articles being analyzed. The results of the review indicate three main themes, namely stress management and psychological well-being, work motivation, and psychology-based leadership and human resource management. These findings confirm that psychology plays a strategic role in improving organizational effectiveness. This study concludes the importance of a holistic approach in management psychology and recommends further, more integrative research.